Dynamically-enhanced strain in atomically thin resonators - Xin Zhang (Nature Portfolio, 2020)
Here, the authors use Raman spectroscopy on circular graphene drums to demonstrate dynamical softening of optical phonons induced by the macroscopic flexural motion of graphene, and find evidence that the strain in graphene is enhanced under non-linear driving.